Current practice of organizing and financing the departmental healthcare system for the military in developed countries: a review - T. P. Bezdenezhnykh; D. V. Lukyantseva (IRBIS LLC, 2018)
Departmental medicine as a Russian-specific healthcare system is currently subject to broad discussions on whether its further support and financing is worthwhile. The Defense Ministry of the Russian Federation has one of the most developed healthcare systems in Russia and thus provides medical care to the military personnel and the veterans. This report aims to review the current practice of organizing and financing the medical assistance for the military in seven developed countries (USA, Uk, Canada, Germany, France, Finland and Singapore) in order to use their experience for the optimization of the Russian military departmental healthcare. This review covers the general principles of healthcare in these countries as well as the specific mechanisms of health care provision for the military.  The Departments of Defense in the reviewed counties have special agencies that provide medical services to the military personnel. The primary role of such agencies is to promote, protect and restore the health of servicemen and servicewomen and to ensure they are ready and fit to perform their missions.  As shown in the present review, the specific details of the medical assistance to the military differ between the countries and largely depend on the overall structure of the national healthcare system.